System prototyping and simulation modelling in mixed farming systems - Booltink, H.W.G.; Thornton, Philip K. (International Livestock Research Institute, 1999)
A project proposal whose aim is to promote more appropriate resource management on smallholder crop-livestock farms in East Africa is described. Prototypes of mixed farming systems will be developed to characterise farming systems according to their management objectives. These prototypes will then be used to map improvements of the farming systems by combining prototyping and simulation modelling. Scenarios will be explored to assess natural resource management interventions that promote sustainability of these prototype-farming systmes. If funded and implemented, the project will result in smallholder prototypes of mixed farming systems in Coastal, Central and Western Kenya, and should provide information concerning viable management options that enhance the productivity and sustainability of smallholders' farming systems.